2018
DOI: 10.1097/md.0000000000009991
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of partial thickness hand burn injuries in children with combination of silver foam dressing and zinc-hyaluronic gel

Abstract: Rationale:Burns is a common type of traumatic injury in childhood. Nowadays, several wound dressings are available to treat the second-degree hand burns conservatively.Patient concerns, diagnoses:At the authors’ institute, 37 children were treated conservatively with a special dressing at first intervention containing Aquacel Ag foam and Zn-hyaluronic gel to determine their effectiveness on partial thickness hand burns.Interventions:The dressing was checked on the second day, and removed on the sixth or sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…According to Jozsa et al [ 11 ], paediatric hand burn injuries more commonly occur in families with lower socioeconomic status, and with these patients, there is also a greater risk of subsequent infection. Although this aspect was not analysed in this study, going forwards, this could be an interesting demographic to look into in detail in further studies, using the Scottish Index of Multiple Deprivation tool as an indicator.…”
Section: Discussionmentioning
confidence: 99%
“…According to Jozsa et al [ 11 ], paediatric hand burn injuries more commonly occur in families with lower socioeconomic status, and with these patients, there is also a greater risk of subsequent infection. Although this aspect was not analysed in this study, going forwards, this could be an interesting demographic to look into in detail in further studies, using the Scottish Index of Multiple Deprivation tool as an indicator.…”
Section: Discussionmentioning
confidence: 99%
“…As an indispensable trace element in the human body, zinc plays a significant role in health and disease. Various zinc-containing products are available for topical application in wound management, such as zinc oxide compression dressings and zinc-hyaluronic gel [16, 17]. In addition, silver and its compounds have been employed for centuries due to their medicinal performance, especially the effects on wound infection control.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, silver and its compounds have been employed for centuries due to their medicinal performance, especially the effects on wound infection control. At present, various silver-based dressings or other wound care productions have emerged as an effective treatment option for infections in burns, open wounds and chronic ulcers [17, 18]. In this research, zinc particles and silver nanoparticles mixed with a biocompatible agglomerant were sprayed on the surface of medical cotton cushion in a dot matrix form to generate low-level ES at the device-wound contact surface in the presence of moisture without the need for any external power supply.…”
Section: Discussionmentioning
confidence: 99%
“…Data from epidemiological studies at specific times can guide the prevention of burns injury and clinical treatment. Previously published studies involving burns to the hand have focused on the treatment and management of specific cases [10][11][12][13]. Few studies have reported the epidemiology of patients with burns to the hands [8,14,15].…”
Section: Introductionmentioning
confidence: 99%